The Effect of Temperature in Cryogenic Treatment on the Mechanical Properties and Microstructure of High-Speed Steel SKH 51 - Hasanah, Indah Uswatun; Alhamidi, A Ali; Andriyansyah, Hardy; Suprapto, Suprapto (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
High-speed steel SKH 51 has excellent mechanical properties, including high hardness and wear resistance. This material is widely used for cutting tools and drills. Service life is also a crucial factor that is often improved to extend the material’s usability. To enhance the service life of SKH 51, a heat treatment modification was applied, specifically cryogenic treatment, to increase its hardness and wear resistance. The process began with austenitization, followed by quenching using N₂ gas. Subsequently, cryogenic treatment was conducted at varying temperatures of -80°C, -110°C, and -140°C, with a holding time of 30 minutes. Finally, a tempering process was done at 540°C with a holding time of 3 hours. The microstructure and mechanical properties after the applied heat treatment were studied. In the as-received condition, the microstructure consisted of pearlite, ferrite, and coarse carbides. After the heat treatment, martensite and carbides formed in significant amounts, with only a small fraction of retained austenite remaining after the cooling process. X-ray diffraction (XRD) analysis revealed carbide phase peaks such as MC, M₂C, and M₆C. The hardness value increased as the cryogenic treatment temperature decreased over the 30-minute duration. Wear resistance was measured using the Oghoshi wear test method, showing an improvement as the cryogenic treatment temperature decreased. The increase in hardness and wear resistance of SKH 51 was attributed to the greater formation of martensite and carbides, which reduced the amount of retained austenite..